Green attitude and economic growth - Ingrid Ott; Susanne Soretz (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2015)
We analyse the interdependence between green attitude and equilibrium development of environmental quality in an endogenous growth model. Individuals take only part of their impact on pollution into account, hence there is a negative externality of capital accumulation on environmental quality. Increasing wealth or increasing pollution enhance green attitude and reduce the externality, because individuals care more about the environment if their income is higher or if pollution is more obvious. The time path of pollution as well as the evolution of equilibrium growth are shown to depend crucially on the determinants of green attitude. If green attitude improves with increasing wealth, e.g. as a consequence of an increase in environmental education, the economy converges to the sustainable growth path and in the long run, also the optimal level of environmental quality is realized. In contrast, pollution remains at a suboptimally high level if individual attitude towards the environment is influenced by pollution itself, that means, if individuals care the more about environmental issues the worse environmental quality.
urn:nbn:de:swb:90-476781
Keywords: O1; O4; Q2; Q5; 330; pollution; endogenous growth; green attitude